Clonal diversity and genetic differentiation in rhizomatous herb, iris japonica (Iridaceae) populations on Jinyun Mountain, Southwest China - Wang, Yong-Jian; Shi, Xue-Ping; Zhong, Zhang-Cheng (Universiti Kebangsaan Malaysia, 2012)
Many plants can reproduce both clonally and sexually, and the relative importance between the two modes of reproduction varied among habitats. Clonal diversity and genetic differentiation of the rhizomatous herb, Iris japonica populations, was analyzed by 12 randomly amplified polymorphic DNA markers to determine the extent that reproductive mode varied locally between two habitats, open area of forest edge (OAFE, 2 populations OAFE 1 and OAFE 2) and bamboo forest (BF, 2 populations BF 1 and BF 2) on Jinyun Mountain, southwest China. Total clonal diversity and genetic diversity of I. japonica populations were high. The clonal diversity and genetic diversity of I. japonica populations in BF habitats were lower than those in OAFE habitats. Neighbor-joining tree by Jaccard’s genetic distance showed two genetically distinct groups: OAFE group and BF group. AMOVA indicated that about half of the total variation existed within the four populations, and that genetic differentiation among habitats (BF populations and OAFE populations) was also significant. OAFE habitats were helpful in maintaining clonal diversity and genetic diversity of I. japonica populations than BF habitats. Habitat differences might have distinguished effects on the relative significance of clonal propagation and sexual reproduction, and further have a fatal influence on clonal diversity, genetic diversity and genetic differentiation of I. japonica populations in Jinyun Mountain, Southwest China.